1994
DOI: 10.1007/bf00301854
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachloroethene metabolism of Dehalospirillum multivorans

Abstract: Dehalospirillum multivorans is a strictly anaerobic bacterium that is able to dechlorinate tetrachloroethene (perchloroethylene; PCE) via trichloroethene (TCE) to cis-1,2-dichloroethene (DCE) as part of its energy metabolism. The present communication describes some features of the dechlorination reaction in growing cultures, cell suspensions, and cell extracts of D. multivorans. Cell suspensions catalyzed the reductive dechlorination of PCE with pyruvate as electron donor at specific rates of up to 150 nmol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(108 citation statements)
references
References 11 publications
2
104
1
1
Order By: Relevance
“…Due to the higher mass of pollutant present, acidification is more likely to occur in the vicinity of the source zone of chlorinated ethenes (8,9). The tolerance of OHRB to low pH has been studied for pure cultures (10)(11)(12)(13)(14)(15)(16)(17)(18) and some consortia containing OHRB (19,20). It has been shown that OHRB are inactivated under acidic conditions (pH Ͻ5), and therefore, pH buffer amendments are required when the aquifer pH is Ͻ5 or when the soil buffering capacity is insufficient (3,9,21).…”
mentioning
confidence: 99%
“…Due to the higher mass of pollutant present, acidification is more likely to occur in the vicinity of the source zone of chlorinated ethenes (8,9). The tolerance of OHRB to low pH has been studied for pure cultures (10)(11)(12)(13)(14)(15)(16)(17)(18) and some consortia containing OHRB (19,20). It has been shown that OHRB are inactivated under acidic conditions (pH Ͻ5), and therefore, pH buffer amendments are required when the aquifer pH is Ͻ5 or when the soil buffering capacity is insufficient (3,9,21).…”
mentioning
confidence: 99%
“…1). The first dataset combines the observations reported by Holliger et al [14] and Neumann et al [15], while the second includes results from Zhuang and Pavlostathis [22]. pH I > 0.5) at pH = 6, and a small amount of residual activity remains at pH = 4.…”
Section: Modelling Approach 21 Fermentation and Dechlorinationmentioning
confidence: 99%
“…The metrics were normalized using the maximum value to facilitate the comparison. The solid line is the function assumed for the AAFB case, while the dashed line is the function fitted to the data from [22] and the dash-dot line is fitted to the data from [14] and [15]. The two behaviours observed in the laboratory experimental data result in significantly different behaviour in the field.…”
Section: Parametermentioning
confidence: 99%
See 2 more Smart Citations